Validation of an instrument to measure the improvement of individual performance in small and medium-sized companies in Mexico - Vasquez-Torres, María del Carmen; García Revilla, Mercedes Raquel; Corral Coronado, Zulema Isabel; Flores López, José Guadalupe (Revista Venezolana de Gerencia, 2024)
The present paper analyzes psychometric properties of a self-made instrument to measure individual performance based on Gilbert’s BEM. This research is quantitative, descriptive, correlational, causal; cross-sectional, using exploratory factor analysis and principal component analysis with Varimax orthogonal rotation. Empirical support was obtained by using a randomly stratified sample of 297 Mexican companies of Sonora State. The questionnaire – named DOPT- proved adequate to assess relevant organizational factors of human performance that could guide organizational performance policies accordingly. Its 40 items assess organizational level achieved in the following areas: Aims and objectives, Feedback, Task support, Incentives, Knowledge/Competences, Context, Sanctions, and Work processes. Psychometric properties results are commented in the light of commented literature about current overall organizational assessment and corporate longevity. In addition, organizational performance areas are discussed under a timing perspective defining mapping and tracing loops of organizational performance management.